2021
DOI: 10.3390/cells10081942
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Anti-SARS-CoV-2 Antibody Responses 3 Months Post Complete Vaccination with BNT162b2; A Prospective Study in 283 Health Workers

Abstract: The aim of this study was to investigate the kinetics of neutralizing antibodies (NAbs) and anti-SARS-CoV-2 anti-S-RBD IgGs up to three months after the second vaccination dose with the BNT162b2 mRNA vaccine. NAbs and anti-S-RBD levels were measured on days 1 (before the first vaccine shot), 8, 22 (before the second shot), 36, 50, and three months after the second vaccination (D111) (NCT04743388). 283 health workers were included in this study. NAbs showed a rapid increase from D8 to D36 at a constant rate of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
28
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 36 publications
5
28
2
Order By: Relevance
“…NAbs against SARS-CoV-2 were measured using an FDA-approved methodology (ELISA, cPass™ SARS-CoV-2 NAbs Detection Kit; GenScript, Piscataway, NJ, USA) [49] on the abovementioned timepoints, as previously described [33,50]. An NAb titer of at least 30% is considered positive, whereas an NAb titer of at least 50% has been associated with clinically relevant viral inhibition [45,[51][52][53]. Samples of the same individual were measured in the same ELISA plate.…”
Section: Nabs Measurementmentioning
confidence: 99%
“…NAbs against SARS-CoV-2 were measured using an FDA-approved methodology (ELISA, cPass™ SARS-CoV-2 NAbs Detection Kit; GenScript, Piscataway, NJ, USA) [49] on the abovementioned timepoints, as previously described [33,50]. An NAb titer of at least 30% is considered positive, whereas an NAb titer of at least 50% has been associated with clinically relevant viral inhibition [45,[51][52][53]. Samples of the same individual were measured in the same ELISA plate.…”
Section: Nabs Measurementmentioning
confidence: 99%
“…Vaccination campaigns against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) are ongoing around the world, with the BNT162b2 mRNA vaccine having a key role in most countries. Although theBNT162b2 is highly efficacious against COVID-19 [1-3], a time-dependent decrease in antibody levels against SARS-CoV-2 has been reported among vaccinated individuals [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…In phase III randomized controlled trials, BNT162b2 has demonstrated an excellent clinical efficacy of 95.0% (95% CI: 90.3-97.6) in adults and 100% (95% CI: 75.3-100) in adolescents [6,7]. Accordingly, neutralizing antibodies, which are a surrogate for clinical efficacy, were three times higher than in convalescent individuals and were detected in approximately 97% of patients after the second injection of BNT162b2 [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%